MEDIA LITERATURE STRATEGY TO COMPETE HOAX ABOUT COVID-19 VACCINE (Case Study: Information Volunteer of Kelompok Informasi Masyarakat Bahari Surabaya City) - Shabrina, Zhafarina (The Commercium, 2022)
The city of Surabaya, which is a metropolitan city, has a fairly high level of information dissemination and understanding but in some areas, there are still many low levels of understanding, especially regarding the covid-19 vaccine. One of them is the fishing village community located in the Sukolilo Baru sub-district which has a relatively low level of education, economy and understanding so it is easy to believe in the Covid-19 vaccine hoax. This study aims to determine the media literacy strategy carried out by KIM Bahari towards the fishing village of Sukolilo Baru in fighting hoaxes related to the Covid-19 vaccine. The method used in this research is a case study and a qualitative descriptive approach with interview techniques in collecting data. The results of this study indicate that to eradicate the Covid-19 vaccine hoax at KIM Bahari, as information volunteers participate in providing literacy, education and socialization in the community so that awareness of hoaxes and vaccine participation increases. KIM Bahari uses three strategies, the first is through the use of digital media, such as providing information, and clarifying information related to the COVID-19 vaccine hoax. The second strategy is to go directly to community groups actively or join various community groups in fishing villages which in its application adjust communication patterns with each audience. The last strategy is to pick up the ball by cooperating with opinion leaders for observation and determining vulnerable groups for easy access and facilitation of the COVID-19 vaccine.Keywords: KIM Bahari, Literacy, Hoax, Covid-19 Pandemic, Vaccines Covid-19, Fisherman's Village